Non-Isolated High-Gain Triple Port DC–DC Buck-Boost Converter With Positive Output Voltage for Photovoltaic Applications - Balaji Chandrasekar; Chellammal Nallaperumal; Sanjeevikumar Padmanaban; Mahajan Sagar Bhaskar; Jens Bo Holm-Nielsen; Zbigniew Leonowicz; Samson O. Masebinu (IEEE Access)
The solar PV based power generation systems are growing faster due to the depletion of fossil fuels and environmental concerns. Combining PV panels and energy buffers such as battery through multi-port converter is one of the viable solutions to deal with the intermittency of PV power. The goal of this paper is to design and analyze the proposed triple port DC-DC buck-boost converter for high step-up/step-down applications. It has two unidirectional ports (port-1 and port-3) and one bi-directional port (port-2) for harnessing photovoltaic energy and charging the battery. At port-1, the combined structure of buck and buck-boost converter is used with a particular arrangement of switches and inductors. The step-up/step-down voltage conversion ratio is higher than the conventional buck-boost converter, and the polarity of the output voltage is maintained positive. The battery is added at the bi-directional port, for the storage of energy through the bi-directional boost converter. The switches operate synchronously for most of the modes making the control strategy simple. The characteristics and modes of operation along with a switching strategy, are elaborated. Experimental results are presented which validate the agreement with the developed theoretical expectation.